New challenges, new possibilities: intergenerational learning and ICT for an ageing society - Patrício, Maria Raquel (2013)
The aim of this article is to analyse EU policy developments in the field of intergenerational learning and ICT for an ageing society and identify learning possibilities in formal, non-formal and informal settings. The need to enhance learning opportunities for older people relates to the overall development of the role of lifelong learning and ICT in the digital society. Firstly, we try to analyse and understand if the policies and consequents practises are enough to promote new possibilities for the new challenges that demographic transformation represents in the world. Secondly, we aim to examine if the intergenerational learning enables best opportunities for the involvement the older in learning ICT. Then we discuss how ICT and intergenerational learning are related, and can support lifelong learning in older ages. Finally, we try to sum up some suggestions to improve ICT and intergenerational learning in order to enable lifelong learning in an ageing society.